AFBYAN I, II, III: making headway in understanding - Youngquist, W (International Center for Tropical Agriculture, 1992)
The African Bean Yield and Adaptation Nurseries (AFBYANs) were designed to facilitate the distribution of elite lines among the national programs in SADC and to supply information on agro-ecological zones and the lines adapted to them. Twenty five entries have been grown in each of the AFBYAN`s (seven entries common to all three) in a total of forty environments. Differences among entries have been detected and the entry by environment interaction is highly significant. In AFBYAN II, Eberhart Russell yield stability parameters were calculated and regression coefficients ranged from 0.56 (Nain de Kyondo, mean yield = 870 kg/ha) to 1.45 (G 12470, mean yield = 1638 kg/ha). Principal components analyses were conducted on the residuals from an analysis of variance on location means. These residuals represent the variation due to the entry by location interaction. The first principal component was found to be highly correlated to latitude of the bean growing environment. This type of analysis permits the quantification of environmental factors that influence genotype performance under different growing conditions